Prevalence of breakthrough COVID-19 infection among healthcare workers in Baghdad - Alaa Ali Salih; Mayasah Abdulleah Sadiq; Waleed Araf Tofeek Al-Ani; Rusul AbdulKareem Mohammed; Hamzah Abdulleh Mohammed (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the prevalence and severity of breakthrough coronavirus disease-2019 infection among health workers, and to assess health workers’ post-vaccination adherence to preventive guidelines. Method: The cross-sectional study was conducted from December 2021 to March 2022 at 2 major hospitals in Baghdad, Iraq, and comprised physicians, pharmacists, dentists and paramedical staff present at time of data collection. The participants were classified according to vaccination status with history of infection. Unvaccinated meant infected before vaccination; partially vaccinated meant infected after the first dose; and fully vaccinated meant breakthrough infection after the second dose. Data was analysed using SPSS 28. Results: Of the 506 participants aged 20-59 years, 327(64.6%) were females, 247(48.8%) were physicians, 72(14.2%) were smokers, and 21(4.1%) had asthma. All the 506(100%) participants had been infected after vaccination; 430(85%) after the second dose, and 76(15%) after the first dose. In 445(88.6%) cases, the infection was mild to moderate, while admission was required in 21(4.1%). With respect to adherence to preventive guidelines, 229(45.3%) subjects were always wearing masks before the vaccination, but 119(23.7%) continued doing that after receiving the second dose of the vaccine. Conclusion: The majority of the participants had fallen victim to breakthrough coronavirus disease-2019 infection. Adherence to preventive guidelines was found to be reduced after the second dose of the vaccination. Key Words: COVID-19, Masks, Pharmacists, Prevalence, Smokers, Vaccination, Physicians, Dentists, Asthma